2017
DOI: 10.5943/mycosphere/8/1/7
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the genus Cytospora and allied species

Abstract: Cytospora species are important plant pathogens causing dieback and canker diseases on a wide range of hosts, worldwide. However, species level identification is difficult due to poor phylogenetic understanding and lack of sequenced type species. ITS sequence data are only available for most Cytospora strains in GenBank. In this study, samples of Cytospora were collected from symptomatic twigs and branches in European Russia. A combination of morphological characters and multi-gene phylogenetic analysis (ITS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 32 publications
4
53
0
2
Order By: Relevance
“…The amplification reactions were carried out with the following protocol: 50 μl reaction volume containing 2 µl of DNA template, 2 µl of each forward and reverse primers, 25 µl of 2 × Bench Top TM Taq Master Mix (mixture of Taq DNA Polymerase (recombinant): 0.05 units/µl, MgCl 2 : 4 mM and dNTPs (dATP, dCTP, dGTP, dTTP): 0.4 mM) and 19 µl of double-distilled water (ddH 2 O) (sterilised water) using the thermal cycle programme in Norphanphoun et al (2017). Purification and sequencing of PCR products with the same primers mentioned above were carried out at Life Biotechnology Co., Shanghai, China.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The amplification reactions were carried out with the following protocol: 50 μl reaction volume containing 2 µl of DNA template, 2 µl of each forward and reverse primers, 25 µl of 2 × Bench Top TM Taq Master Mix (mixture of Taq DNA Polymerase (recombinant): 0.05 units/µl, MgCl 2 : 4 mM and dNTPs (dATP, dCTP, dGTP, dTTP): 0.4 mM) and 19 µl of double-distilled water (ddH 2 O) (sterilised water) using the thermal cycle programme in Norphanphoun et al (2017). Purification and sequencing of PCR products with the same primers mentioned above were carried out at Life Biotechnology Co., Shanghai, China.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, there are 614 epithets for Cytospora (Index Fungorum 2018, 14 June 2018) with an estimated 110 species in Kirk et al (2008). Recently, fourteen new species were introduced to this genus by Norphanphoun et al (2017). In this study, we report on three novel species of Cytospora associated with mangroves in Thailand.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…1). In the past five years alone, the polyphasic approach (morphological identification and phylogenetic species recognition concept) has led to the descriptions of additional new species of Cytospora in China (Wang et al 2013;Zhang et al 2014;Fan et al 2014aFan et al , 2014bFan et al , 2015aFan et al , 2015bYang et al 2015;Lawrence et al 2017;Norphanphoun et al 2017), which were included here. The current study indicated that the Cytospora spiraeae represents a novel species with high support value (MP/ML/BI = 100/100/1) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…More than 600 species epithets named Cytospora have been recorded in Index Fungorum (2017) with an estimated 110 species in Kirk et al (2008). Recent studies have subsequently emphasized on part of Cytospora species using multiphase approaches to solve the confused frame (Fan et al 2014a(Fan et al , 2014b(Fan et al , 2015a(Fan et al , 2015bYang et al 2015;Lawrence et al 2017;Norphanphoun et al 2017). However, only ITS gene are available for most known Cytospora species, and extype sequence data are available for only a very few species and many taxa need epitypifying (Adams et al 2005).…”
Section: Introductionmentioning
confidence: 99%